Helena Paz-Elena Garro: La Memoria Compartida - Alba Villalobos, Ana María (Acta Universitaria, 2008)
This text analyzes Helena Paz’s Memoirs, in the light of the autobiographical and biographical texts about Elena Garro’s life. The thesis of the text is that there are many elements supporting the statement that a substantial part of Elena Garro’s unedited memoirs are found inserted in her daughter’s (Helena Paz’s) Memoirs. Arguments for such an assertion are presented, together with the excerpts which would correspond more to the experiences of the mother than to those of the daughter.